PENGURUSAN NOMOR INDUK BERUSAHA (NIB) BAGI PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) (Jurnal PkM Pemberdayaan Masyarakat, 2022)
Sukaratu Urban Village, Pagelaran District, is one of the urban villages that have a number of UMKM from various types of businesses such as culinary, grocery stores, laundry, and convection. However, there are still many UMKM who do not have a Nomor Induk Berusaha (NIB) due to a lack of socialization and public ignorance about NIB. Therefore, in this community service, KKNT STMIK PRINGSEWU provided assistance in making the Nomor Induk Berusaha (NIB) for UMKM in Suka Ratu Urban Village. The purpose of this community service is to help UMKM to have NIB. The method used in the mentoring program for making NIB is first, collecting data on the number of UMKM who do not yet have a NIB. Secondly, conduct socialization and assistance in making NIB for UMKM. Thirdly, the creation of NIB for UMKM. Fourthly, submission of NIB documents to UMKM. There are positive results in this community service. Firstly, as many as 5 UMKM actors now have a NIB. Secondly, UMKM actors know the NIB and the importance of having a business